Soil total carbon as a key factor affects soil biota attributes in plant mixtures over time: A meta-analysis - Huiling Zhang; Jinshan Cai; Xu Yang; Jing Huang; Xuan Zhou; Dima Chen (Geoderma)
Studies have determined that soil biota have distinct responses to plant richness. However, the potential mechanisms that regulate soil biota (microbes and fauna) attributes (biomass, activity, and abundance) to plant mixtures over experimental time are still unclear. By conducting 1594 paired observations of the impacts of plant mixture on soil biota attributes and its corresponding potential drivers from 179 studies, we found that plant above- and belowground biomass and total biomass were significantly increased by 35.0%, 52.9%, and 48.6% under plant mixture, respectively. Soil pH decreased significantly by 0.8% with experimental time. The responses of soil microbial attributes were more sensitive than soil fauna abundances under plant mixture over time. On average, soil microbial respiration and microbial biomass increased by 11.6% and 12.1%, respectively, in plant mixtures across all ecosystem types. For soil fauna community, only the abundance of herbivores showed a significant increase of 20.4% to plant mixtures. The response of above- and belowground biomass, total biomass, the ratio of carbon to nitrogen, and pH showed positive relationships with most specific microbial attributes, while mean annual precipitation, mean annual temperature, and the response of soil total nitrogen and NO3–-N showed negative relationships with them in response to plant mixtures. The abundance of soil fauna was secondarily affected by the changes of soil abiotic properties. Taken together, the response of soil total carbon had a strong effect on soil biota attributes. Changes in belowground biomass and total biomass showed negative relationships with specific soil fauna abundance, while soil total carbon, nitrogen, pH, and soil moisture showed positive relationships with specific soil fauna abundance. However, only herbivore abundance showed significant differences across different ecosystems. Our analysis illustrates the distinct responses of soil biota attributes to plant mixtures and their potential influencing factors, thereby benefiting the sustainability of soil biota biodiversity in the face of plant richness loss.